Legal Analysis of the Position of Academic Papers in the Formulation of Regional Regulations According to the Law on the Formation of Legislation - Citra Dewi (Program Pascasarjana Universitas Muhammadiyah Palu, 2025)
The issues studied are the legal position of academic papers in the formulation of regional regulations in Indonesia and the legal implications of draft regional regulations that are not accompanied by academic papers. The aim of this research is to understand and analyze the legal position of academic papers in the formulation of regional regulations in Indonesia, as well as to analyze the legal implications of draft regulations that lack academic papers. This study uses normative legal research, examining laws, legal principles, legal theories, legal materials, and library sources. The findings show that, legally, academic papers are not merely complementary administrative documents but substantive requirements attached to the legitimacy of the process of forming regional regulations. Academic papers bridge the gap between normative needs and empirical realities. The absence of academic papers may cause formal defects in the process of forming regulations, which could result in cancellation by the central government through evaluation or annulment by the Supreme Court through judicial review.